Experimental Investigations of the Depth Filtration inside Open‐Cell Foam Filters Supported by High‐Resolution Computed Tomography Scanning and Pore‐Scale Numerical Simulations. Issue 2 (25th October 2019) - Hoppach, Daniel; Werzner, Eric; Demuth, Cornelius; Löwer, Erik; Lehmann, Henry; Ditscherlein, Lisa; Ditscherlein, Ralf; Peuker, Urs A.; Ray, Subhashis
Abstract : The removal of nonmetallic inclusions from metal melts is a crucial step in producing high‐quality castings that have to meet strict requirements regarding strength, toughness, and machinability. To separate the unwanted impurities, the liquid metal is usually passed through ceramic foam filters (CFF), in which the inclusions adhere to the surface of a complex strut network. The development of improved CFF structures requires a good understanding of the physical phenomena involved in the filtration process. In this respect, an experimental investigation of the real system is challenging, due to the opacity of the melt, high temperature, and the presence of a protective atmosphere. Therefore, the present study relies on water model experiments, which are conducted for different pore counts and flow velocities. To achieve a high degree of similarity to the real system, the wetting properties of the filters and particles are adjusted accordingly. Experimentally evaluated filtration efficiencies are compared with predictions obtained from a detailed numerical model that considers the CFF geometry, which is digitized using 3D X‐Ray micro‐computed tomography, and previously measured particle adhesion forces. The results suggest that a considerable fraction of particles does not remain attached after collision with the CFF struts. Abstract : Understanding the removal of nonmetallic inclusions inside ceramic foam filters (CFF) is a basic requirement for increasing filtration efficiency. To clarify the physical phenomena involved in the filtration process, water model experiments with actual CFF geometry, 3D X‐Ray tomography, a detailed numerical simulation, as well as atomic force microscopy for evaluation of particle adhesion forces, are used.